Judges 19-21 and Ruth : Canon as a Voice of Answerability - Matheny, Jennifer M., (Biblical Interpretation Series ;, 2022)
Judges 19-21 is filled with sexual violence, silent victims, and the lack of an ethical response. Utilizing a Bakhtinian-canonical perspective, this book seeks alternative canonical voices of answerability and non-violence through dialogue with the book of Ruth.